2010
DOI: 10.1080/10942910902895218
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Functions ofE- ANDZ-Ajoene Derived from Japanese Garlic

Abstract: Antioxidative activities of E-and Z-ajoene prepared from Japanese garlic were studied using various radical scavenging effects. Among the various antioxidative activities tested, ajoene was found to show the highest hydroxyl radicals scavenging activity (E-ajoene = 50% and Z-ajoene = 63%). These ajoene were 5.2-13 times less efficient at reducing DPPH radical and 1.1-1.4 times less efficient at hydroxyl radical as compared with authentic αtocopherol. Essentially E-and Z-ajoene were capable of scavenging supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Antioxidant activity was measured by the scavenging capacity of the stable 2, 2-diphenyl-1 picryl hydrazyl (DPPH) free radical assays [27,28]. Briefly, 25 µL of appropriately diluted samples were added to 200 µL of DPPH solution (dissolved in methanol) in a well of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity was measured by the scavenging capacity of the stable 2, 2-diphenyl-1 picryl hydrazyl (DPPH) free radical assays [27,28]. Briefly, 25 µL of appropriately diluted samples were added to 200 µL of DPPH solution (dissolved in methanol) in a well of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported in literature that Z-ajoene possesses better antimicrobial and antioxidant activity than E-ajoene. [ 12 29 ] However, in our study we observed that E-ajoene showed anti-tubercular activity at 125–250 μg/mL and Z-ajoene was inactive at the highest concentration evaluated i.e., 250 μg/mL. This may be possibly due to degradation of Z-ajoene after incubation at 37°C for 7 days.…”
Section: Resultsmentioning
confidence: 51%
“…In alternative medicine, garlic is used as a stimulant of the immune system and non-aggressive natural antibiotic for intestinal flora [14]. This condiment shows antifungal, antibacterial, antiviral, immunostimulatory, antiaggregatory, hypotensive, and antioxidant properties [14,15], being, therefore, recommended for the treatment of parasitic infections, microbial infections, cardiovascular diseases (arteriosclerosis, hyperlipidemia, stroke, hypertension, and diabetes), immunodepressive diseases, and cancer [16][17][18][19]. Such medicinal properties have been attributed to organosulfur compounds present in garlic [14].…”
Section: Introductionmentioning
confidence: 99%